Acceptance and use of information and communication technology by academicians: Towards a conceptual framework - Chandio, Shahmurad; Abu Seman, Muhamad Sadry; Samsuri, Suhaila; Shah, Asadullah (IEEE, 2016)
Information and Communication Technology (ICT) has changed the world scenario including business and economies. There are new opportunities and challenges for every country to produce knowledge oriented citizens. Driven by these changes, numerous higher education institutions around the world are integrating and adopting latest ICT tools to deliver quality education. However, the Effectiveness of a new technologies introduced in educational institution depends on acceptance and utilization by academicians in the academic institutions. Thus realizing the importance of ICT availability and adoption in developed countries, this research is aimed to understand and assess the ICT adoption in Pakistan. This study also focuses on fundamental literature to investigate the critical success factors and propose a model for ICT adoption by academicians of higher education institutions in Pakistan. The contribution of this research improves the quality of education system in developing countries by effectively utilizing ICT in higher education institutions.